SOSIALISASI PENCEGAHAN DIARE PADA ANAK USIA SEKOLAH DENGAN MEDIA PUZZLE DI SMP METHODIST 1 KUTALIMBARU KABUPATEN DELI SERDANG - Amirah, Nada; Azhary, Muhammad Rifqi; Sitio, Sri Sudewi; Putri, rizqi Nanda; Tanjung, Lina Febriani; Damanik, Yunita Syahputri (INSTITUT KESEHATAN DELI HUSADA, 2024)
Diarrhea is an environmental disease that occurs in almost all geographical areas in the world and is always present at every level of society. The emergence of diarrhea is caused by multifactors that need to be known and understood by society, starting from the smallest sphere, namely the family. School-aged children are one of the targets for being given knowledge regarding diarrhea prevention so that they can take this knowledge to their families for faster dissemination of information. However, providing information using the material method alone is not good enough to attract school-age interest in learning something, so in this community service, puzzle media is used so that students can play while learning to understand the factors that cause diarrhea and preventive measures against it. This socialization using puzzle media was applied to students in grades VII, VIII, and IX of SMP Methodist 1 Kutalimbaru. Students are divided into groups consisting of 3 participants, each group is allowed to put the pictures together on the puzzle and answer the questions on the puzzle board before attaching them. Each participant was also asked to explain the material contained in the puzzle to measure their level of knowledge regarding diarrhea and its prevention. This method is considered effective in providing knowledge to students. Students look enthusiastic about learning while playing with puzzle media so that they can easily understand and remember the material presented by the instructor.